Orientation of herpes simplex virus type 1 immediate early mRNA's. - Clements, J B (1979)
We have determined the orientation of 4 immediate early (IE) mRNA's on the herpes simplex virus type 1 genome by mapping cDNA's complementary to the 3'-termini of messages. These IE mRNA's are transcribed by a pre-existing cell RNA polymerase, and we propose a model which allows their synthesis from a circular template using a single virus promoter region. The promoter region, which is located in the two repetitive DNA regions which flank the short unique region of the virus genome, may serve to initiate bidirectional transcription of these IE mRNA's.